A framework for personal protective equipment use in laboratories: regulatory compliance and employee protection - Pillai, Segaran P.; Bradberry, Sarah; Newcomer, Marisa; Pittas, Tanya; Mathern, Kelsey (Frontiers in Public Health, 2025)
The Occupational Safety and Health Administration (OSHA) Personal Protective Equipment (PPE) Standard, outlined in 29 CFR 1910 Subpart I states that Protective gear - including personal protective clothing, respiratory equipment, and barriers or shields- must be supplied, properly used, and kept clean and functional whenever there are hazards present. These hazards may arise from processes, environmental conditions, chemicals, radiation, or mechanical sources that could potentially cause injury or harm bodily functions through skin contact, inhalation, or absorption. Employers must supply PPE to their employees as determined by hazard assessments of the workplace and duties performed by employees. Employees for their part are required to use PPE as instructed to reduce exposure to occupational hazards and the likelihood of injury or illness, as appropriate. PPE includes all clothing (e.g., coats, gowns, gloves, shoe covers, boots) and other work accessories (e.g., respirators, face shields, safety glasses, goggles) intended to act as a barrier against workplace hazards or to be worn for protection, serving as the last line of defense in the hierarchy of safety controls. The OSHA PPE Standard includes requirements for selection of equipment, training requirements, records management, PPE selection guidelines and potential risk and hazard assessment. OSHA has standards that require such equipment meet or be equivalent to standards developed by the National Institute for Occupational Safety and Health (NIOSH) or the American National Standards Institute (ANSI). This article provides an overview of the types of PPE, and considerations for their selection and use to address laboratory hazards.